A double‐blind, randomized, multicenter phase 3 study of palonosetron vs granisetron combined with dexamethasone and fosaprepitant to prevent chemotherapy‐induced nausea and vomiting in patients with breast cancer receiving anthracycline and cyclophosphamide. (13th March 2020) - Matsumoto, Koji; Takahashi, Masato; Sato, Kazuhiko; Osaki, Akihiko; Takano, Toshimi; Naito, Yoichi; Matsuura, Kazuo; Aogi, Kenjiro; Fujiwara, Kimiko; Tamura, Kenji; Baba, Motoi; Tokunaga, Shinya; et al.
Abstract: Purpose: To investigate whether palonosetron is better than granisetron in preventing chemotherapy‐induced nausea and vomiting (CINV) in a three‐drug combination with dexamethasone and fosaprepitant (Fos) in patients with breast cancer who are placed on anthracycline and cyclophosphamide (AC‐based regimen). Patients and Methods: Chemo‐naive women with primary breast cancer were randomly administered either palonosetron 0.75 mg (day 1) or granisetron 1 mg (day 1) combined with dexamethasone (12 mg at day 1, 8 mg at day 2 and day 3) and Fos 150 mg (day 1) before receiving AC‐based regimen in a double‐blind study. The primary endpoint was the complete response (CR) rate of emesis in cycle 1 in the delayed phase. This was defined as neither vomiting nor rescue drug usage for emesis at >24‐120 hours after chemotherapy. Secondary endpoints were the CR in the acute/overall phase (0‐24/0‐120 hours, respectively, after chemotherapy), no nausea and vomiting, Patient‐Reported Outcomes version of the Common Terminology Criteria for Adverse Events (PRO‐CTCAE), and safety. Results: From December 2012 to October 2014, 326 patients were treated and evaluated (164/162 evaluable patients in granisetron/palonosetron arm, respectively). The CR during the delayed phase was 60.4% in the granisetron regimen and 62.3% in the palonosetron regimen. The CR during acute phase (73.2% vs 75.9%, respectively) and the CR during overall phase (54.9% in both regimens) were very identical. A significantly higher number of patients in the palonosetron arm were free from nausea during the delayed phase (28% vs 40.1%; P  = .029). Adverse events were also identical, although infusion site reactions (ISR) were higher (20.3%‐23.3%) than preceding studies in both regimens. Conclusion: In combination with dexamethasone and Fos, this study suggests that palonosetron is not better than granisetron in chemo‐naive patients with primary breast cancer receiving AC‐based regimen. Administration of Fos in peripheral veins after AC‐based regimen increased ISR. Abstract : A randomized phase 3 trial compared palonosetron with granisetron as combination therapy with dexamethasone and fosaprepitant for chemotherapy‐induced nausea and vomiting prevention in breast cancer patients receiving anthracycline and cyclophosphamide. Although palonosetron was better than granisetron in terms of control of nausea in the delayed phase, the primary endpoint, CR in the delayed phase, was not statistically significant (62.3% vs 60.4%).